On Some Features and Functions of Tropes in Patristic Heritage of Saints Tikhon of Zadonsk and Ignatius Bryanchaninov - P. A. Kolobaev (Научный диалог, 2019)
The features of tropes functioning (metaphor, comparison and allegory) are considered on the material of patristic heritage of saints Tikhon of Zadonsk and Ignatius Bryanchaninov. The relevance of this study is determined by the need to study the expressive means of language in the Church-religious style and religious communication. Classification of language models of comparison in the spiritual prose of Saint Tikhon of Zadonsk is given: (1) the model of “secular / spiritual”; (2) the model of “Christ / Christians”, representatives of which are the tokens God , heavenly Father , Christ / children ( Christians ); (3) the “heart / vessel” model by which a human heart is compared to a corporeal image of a receptacle. The following functions of tropes in the works of saints Tikhon of Zadonsk and Ignatius Bryanchaninov are distinguished: sense-forming, helping to create a coherent picture, bringing reader to a better understanding of the deep moral and spiritual meanings laid by the author; text-forming, which is manifested in the conceptualization of the biblical image. Grammatical means frequent in patristic text are described: imperative and etiquette formulas of address. The novelty of the study is seen in the author’s appeal to the insufficiently studied in the linguistic and stylistic aspect texts of patristic literature of the 18th-19th centuries. The most important stylistic feature of the authors’ creativity - theocentrism - is revealed. It is proved that metaphor and comparison in religious discourse act as a means of translation of fundamental spiritual values for the Russian national consciousness.